Measurement of the Uranium Concentration in Different Types of Tea Used in Iraqi Kitchen - S. Shafik, Shafik; K. Rejah, Basim (Iraqi Journal of Science, 2023)
Tea is one of the important liquids that people drink. In Iraq, tea is the main beverage after water. The tea plant is known scientifically as Camellia sinensis, when planting and during growth needs to fertilizers, which contents remarkable amounts of Uranium. So it became important to study the concentrations of uranium found in tea. Eight samples of tea had been taking, which represent the most important species used in the Iraqi kitchen, and the Uranium concentrations were measured. The results showed that the average concentration of uranium for all samples were1.005 mg/L, while the average of the annual effective dose was 0.221 mSν/y. The results also indicated that green tea possesses small concentration of Uranium compared with other species.